1997
DOI: 10.1046/j.1365-2249.1997.d01-894.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to endothelial cells in Kawasaki disease lyse endothelial cells without cytokine pretreatment

Abstract: SUMMARYKawasaki disease (KD) is characterized by diffuse vasculitis and marked immune activation. To confirm the presence of antiendothelial cell antibodies (AECA) and cytotoxicity of AECA, we investigated the presence of AECA using ELISA and cytotoxicity of AECA in KD. Sera from patients with acute KD were assessed for binding to human umbilical vein endothelial cells (HUVEC) using a cell-based ELISA, and for cytotoxicity against HUVEC as indicated by the conversion of a tetrazolium salt (MTT) into a coloured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
45
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 12 publications
4
45
0
Order By: Relevance
“…10 Antiendothelial cell antibodies have a role in a complement system or antibody-related endothelial cell cytotoxicity. [11][12][13] They are detected in serum samples from patients with certain diseases (such as Wegener granulomatosis, Takayasu arteritis, and Kawasaki syndrome) in which varying degrees of vascular wall injury are associated. Vasculitis is rare in patients without AECAs who have positive antineutrophil cytoplasmic antibodies, while the presence of AECAs is associated with an increased incidence of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…10 Antiendothelial cell antibodies have a role in a complement system or antibody-related endothelial cell cytotoxicity. [11][12][13] They are detected in serum samples from patients with certain diseases (such as Wegener granulomatosis, Takayasu arteritis, and Kawasaki syndrome) in which varying degrees of vascular wall injury are associated. Vasculitis is rare in patients without AECAs who have positive antineutrophil cytoplasmic antibodies, while the presence of AECAs is associated with an increased incidence of vasculitis.…”
Section: Discussionmentioning
confidence: 99%
“…In vasculitides, it was suggested that endothelium was not only the target of injury, but also an active participant of vasculitic damage [9]. Anti-endothelial cell antibodies (AECA) have been described in various autoimmune and vasculitic disorders [10][11][12][13][14][15][16][17][18]. They have been implicated in the pathogenesis of vascular injury common to these disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have demonstrated the presence of cytotoxic anti-endothelial cell antibodies in the serum of patients with Kawasaki's disease (30,31,32), hemolytic-uremic syndrome (33), and individuals with carotid atherosclerosis (34). Since mAb 3.B6 reacted with human valve endothelium, we determined if mAb 3.B6 was cytotoxic for endothelial cells.…”
mentioning
confidence: 97%